Optimization Of Ferulic Acid Extraction From Banana Stem Waste - N., Zainol; S. N., Ismail (Global Science Publications, 2014)
This work deals with the mechanical extraction of banana stem by using sugar cane press machine for the extraction of ferulic acid (FA). Central Composite Design (CCD) with five replicates at the center point was used to investigate the simultaneous effect of the variables: pretreatment temperature (20-30oC) and storage time for extraction juice (20 -24 h) on the FA extraction. The FA was analysed by using high performance liquid chromatography (HPLC) and FA yield were found ranging from 1.101x10-4 to 2.274x10-4g/g. Quadratic model was well fitted (R2>0.90) to the experimental data to describe the extraction of FA as a function of the operational variables employed. The best FA extraction was during the pretreatment at 25oC and 24 h storage time for extraction juice. Under this condition, banana stem juice containing 2.274x10-4 g/g FA was obtained.